Triangular systems and a generalization of primitive polynomials. (May 2015) - Angermüller, Gerhard
Abstract: A well-known generalization of the notion of primitive polynomials over factorial domains to arbitrary commutative rings is analyzed and applied to triangular systems. In particular, we clarify when a triangular system generates its saturation ideal, thus correcting a criterion published first in 2008.